2016
DOI: 10.1007/s13277-016-5181-0
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected frequency of genomic alterations in histologically normal colonic tissue from colon cancer patients

Abstract: As shown by genomic studies, colorectal cancer (CRC) is a highly heterogeneous disease, where copy number alterations (CNAs) may greatly vary among different patients. To explore whether CNAs may be present also in histologically normal tissues from patients affected by CRC, we performed CGH + SNP Microarray on 15 paired tumoral and normal samples. Here, we report for the first time the occurrence of CNAs as a common feature of the histologically normal tissue from CRC patients, particularly CNAs affecting dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…APC, KRAS, TP53) (data not shown). This result is in agreement with a recent manuscript showing the occurrence of CNAs as a common feature of the histologically normal tissue from CRC patients [ 23 ]. For this reason, the filtering of germline variants, for the identification of true somatic mutations, was performed by pooling the variants detected in the 13 PBL samples, generating a “virtual pool” of germline variants as previously described [ 24 27 ].…”
Section: Resultssupporting
confidence: 94%
“…APC, KRAS, TP53) (data not shown). This result is in agreement with a recent manuscript showing the occurrence of CNAs as a common feature of the histologically normal tissue from CRC patients [ 23 ]. For this reason, the filtering of germline variants, for the identification of true somatic mutations, was performed by pooling the variants detected in the 13 PBL samples, generating a “virtual pool” of germline variants as previously described [ 24 27 ].…”
Section: Resultssupporting
confidence: 94%
“…Cancer is thought to proceed through a multi-step process where accumulating alterations in driver genes allow cells to clonally expand and invade surrounding tissues 34 . A limited number of RNA and DNA sequencing studies interrogating a range of precancerous tissues from the breast 3539 , colon 4044 , lung 45,46 , head and neck 47 , skin 48,49 , and esophagus 5055 have indicated that the path to cancer development is context-specific and involves diverse processes. Thesey studies suggest that early lesions are polyclonal and driver mutations present in late-stage disease, and that tumor development occurs via large-scale genomic rearrangements and copy number changes.…”
Section: Novel Genomic Approaches For Cancer Screeningmentioning
confidence: 99%
“…A clear proof of that, concerning for instance the trophoblastic program, is the reproductive cloning through somatic cell nuclear transfer, which leads to all the intra- and extra-embryonic structures, and in particular the placenta. The probability of completion of malignant transdifferentiation is supposed to be infinitely small as compared to the rate of potentially oncogenic mutations ( 10 13 ). This matches the fact that the cancer rate in the population would otherwise be disproportionate to the observed one.…”
Section: Malignant Transdifferentiationmentioning
confidence: 99%